A Rare Case of Urethral Tuberculosis - D. P. Kholtobin; E. V. Kulchavenya (Туберкулез и болезни лёгких)
Urethral tuberculosis is a rare disease since the advent of highly effective anti-tuberculosis drugs. The article describes an extremely rare clinical observation of a 34-year-old patient with the transition of tuberculous inflammation from the subcutaneous tissue to the wall of the urethra with intact kidneys. Since the first blood discharge from the urethra, the diagnostic process took 3.5 years, all these years, multiple examinations for tuberculosis were carried out and the results were negative, while the disease progressed. The diagnosis was differentiated between acute purulent anterior subcutaneous paraproctitis and festering pararectal cyst. There were repeated openings of the perineal abscess, no bacterial growth was observed, histological tests revealed chronic purulent inflammation. In view of the persistent recurrent course of perineal abscess, tuberculosis was repeatedly suspected. Acid-resistant mycobacteria were found in the discharge from the fistula by fluorescent microscopy: 10-99 in the sample. Tuberculous mycobacteria were not found in the urine by polymerase chain reaction. The patient was diagnosed with A18.4. Tuberculosis of subcutaneous fat (perineum). Mycobacterium tuberculosis (+). The course of disease was complicated by perineal fistula. With the anti-tuberculosis treatment, the fistulous opening healed within a month.